How have the Challenges Faced by Gauteng-based Township Small Business Evolved since Covid-19? - Msimango-Galawe, Jabulile; Mohodi-Nteo, Lerato Palesa (Universitas Proklamasi 45, 2024)
This study examines the evolving challenges and potential solutions for township-based small, medium, and micro enterprises (SMMEs) in Gauteng, South Africa which are crucial in mitigating poverty and unemployment. Historically, SMMEs in townships were overlooked by policymakers, limiting their growth and sustainability. Through semi-structured interviews with 18 SMME owners, this study reveals that while some challenges remain consistent, they have shifted in nature. Before Covid-19, internal factors such as financial management, business operations, and human resources were predominant obstacles. Post-pandemic, however, external factors such as market survival, consumer buying power, and heightened unemployment emerged as significant threats. The pandemic left SMMEs in survival mode, with many unable to attract customers due to the declining purchasing power of their communities. Notably, mental health issues among business owners became a pressing concern, highlighting a need for psychological support. The study identifies job creation, skill development, and accessible government funding as essential solutions for fostering SMME resilience. Addressing these evolving challenges with targeted support could enhance the stability and growth of township SMMEs, promoting economic empowerment in the long term. The findings underscore the importance of adapting policies to the shifting needs of SMMEs in a post-pandemic landscape.